2004
DOI: 10.1159/000080376
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Gender and Region on Responses to 5-HT in the Rat Small Intestine

Abstract: The aim of this study was to obtain more information regarding the ‘atypical’ 5-HT7 receptor of the rat jejunum. 5-HT7-induced contractions of the jejunum were elicited by 5-HT in the presence of ondansetron. Maximal responses were slightly larger in tissues from male compared to female rats of comparable age, with Emax values of 97.2 ± 3.3 and 84.25 ± 4.3% respectively compared to acetylcholine as an internal standard. However, the pEC50 valuesfor 5-HT we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2006
2006
2007
2007

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…The rat jejunum and ileum were used to establish the conditions for studying the 5‐HT 3 ‐induced responses by adding antagonists to the bathing solution to block nontarget 5‐HT receptors. The nontarget 5‐HT receptors are the 5‐HT 2A (Briejer et al ., 1997) and 5‐HT 4 receptors of the rat ileum (Tuladhar et al ., 1996) and colon (Kadowaki et al ., 2002) and the ‘atypical’ 5‐HT 7 receptor of the rat jejunum (McLean & Coupar, 1996; Liu et al ., 2004). Therefore, we investigated the effects of methysergide, which is an antagonist at 5‐HT 1,2,5,6,7 receptors (Hoyer et al ., 1994) and GR125487, which is a 5‐HT 4 receptor antagonist (Gale et al ., 1994) using the rat jejunum and ileum.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The rat jejunum and ileum were used to establish the conditions for studying the 5‐HT 3 ‐induced responses by adding antagonists to the bathing solution to block nontarget 5‐HT receptors. The nontarget 5‐HT receptors are the 5‐HT 2A (Briejer et al ., 1997) and 5‐HT 4 receptors of the rat ileum (Tuladhar et al ., 1996) and colon (Kadowaki et al ., 2002) and the ‘atypical’ 5‐HT 7 receptor of the rat jejunum (McLean & Coupar, 1996; Liu et al ., 2004). Therefore, we investigated the effects of methysergide, which is an antagonist at 5‐HT 1,2,5,6,7 receptors (Hoyer et al ., 1994) and GR125487, which is a 5‐HT 4 receptor antagonist (Gale et al ., 1994) using the rat jejunum and ileum.…”
Section: Resultsmentioning
confidence: 99%
“…The fraction of the first curve was 0.57 with a pEC 50 of 7.13±0.09 ( n =8), whereas the pEC 50 of the second phase was 5.8±0.07 ( n =8). Previously, we had shown that the first phase is due to the activation of an ‘atypical’ 5‐HT 7 receptor population in the longitudinal muscle demonstrated by the presence of mRNA and functional properties (McLean & Coupar, 1996; Hemedah et al ., 1999; Liu et al ., 2004), whereas the second phase, shown at concentrations of 5‐HT above 1 μ M , is due to activation of neuronal 5‐HT 3 receptors (McLean & Coupar, 1996). Responses to 5‐HT were reduced by methysergide (1 μ M ) and GR125487 (0.1 μ M ) alone, but the combination of the antagonists at the same concentrations limited the 5‐HT response to a monophasic curve with an E max value of 35.72±1.6 and pEC 50 of 5.95±0.07 ( n =10, Figure 2a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, SB-269970 may be tissueselective. To illustrate this, we have found that SB-269970 does not inhibit 5-HT 7 -mediated contractions of the rat jejunum preparation (Liu, Irving and Coupar, unpublished results) even though whole tissues and longitudinal muscle showed the presence of mRNA for the r5-HT 7 receptor, particularly the r5-HT 7(a) and r5-HT 7(b) isoforms (Liu et al, 2004). However, this should be balanced against the generally agreed view that SB-269970 is not a species-selective antagonist.…”
Section: Discussionmentioning
confidence: 99%
“…When studying the 5-HT signaling pathway, important elements to examine include the number of EC cells, 5-HT content, tryptophan hydroxylase level, 5-hydroxyindoleacedic acid (HIAA), plasma 5-HT concentration and SERT expression [12] . Studies on animals and humans have measured the above elements in gastric and small intestinal mucosa and drawn some meaningful conclusions with regard to the mucosa 5-HT signaling pathway [13][14][15] . In this study, two important indicators, EC cells and 5-HT content, were used to study the small intestinal 5-HT signaling pathway in IBS patients.…”
Section: Discussionmentioning
confidence: 99%